Feeding Practices and Its Association with nutritional status among Infants of Working Mothers of a Bangladeshi Garments Factory (Northern International Medical College Journal, 2025)
Background: Breastfeeding is considered as one of the most important factors for growth and development of infants, which offers tremendous health benefits to both child and mother. Breastfeeding provides all the energy and nutrients that the infant needs for the first 6 months of life and it continues to provide up to half or more of a child’s nutritional needs during the second half of the first year and up to one third during the second year of life. Objective:This study determinesthe feeding practices and its association with nutritional status among the infants of working mothers in a selected garments factory of Bangladesh. Methods: This cross-sectional study on 267 working womenwith infants aged 0 to 12 months of Garments Factory in Narayangonj was carried out at the Department of Pediatrics, Institute of Child and Mother Health (ICMH), Matuail, Dhaka.After takinga written consent of the study subjects were enrolled in the study. A detail history was taken regarding breastfeeding practices and complementary feeding as well as co-morbidities. Then anthropometry of infants was measured and plotted in CDC growth chart. Nutritional status was determinedby using Z-scores for weight-for-age (WAZ), weight-for-length (WLZ), length-for-age (LAZ). Z-scores of